Comprehensive Analysis of Transcriptome Sequencing Data in the Lung Tissues of COPD Subjects. (5th March 2015) - Kim, Woo Jin; Lim, Jae Hyun; Lee, Jae Seung; Lee, Sang-Do; Kim, Ju Han; Oh, Yeon-Mok
Abstract : Background and Objectives. Chronic obstructive pulmonary disease (COPD) is a complex disease characterized by airflow limitation. Although airway inflammation and oxidative stress are known to be important in the pathogenesis of COPD, the mechanism underlying airflow obstruction is not fully understood. Gene expression profiling of lung tissue was performed to define the molecular pathways that are dysregulated in COPD. Methods. RNA was isolated from lung tissues obtained from 98 subjects with COPD and 91 control subjects with normal spirometry. The RNA samples were processed with RNA-seq using the HiSeq 2000 system. Genes expressed differentially between the two groups were identified using Student's t -test. Results. After filtering for genes with zero counts and noncoding genes, 16, 676 genes were evaluated. A total of 2312 genes were differentially expressed between the lung tissues of COPD and control subjects (false discovery rate correctedq < 0.01 ). The expression of genes related to oxidative phosphorylation and protein catabolism was reduced and genes related to chromatin modification were dysregulated in lung tissues of COPD subjects. Conclusions . Oxidative phosphorylation, protein degradation, and chromatin modification were the most dysregulated pathways in the lung tissues of COPD subjects. These findings may have clinical and mechanistic implications in COPD.